PERANAN LEMBAGA BESLAG DAN PELAKSANAANNYA DALAM PERKARA PERDATA DI WILAYAH HUKUM PENGADILAN NEGERI JAMBI - Fachruddin Razi (Universitas Batanghari Jambi, 2009)
The purpose of this researc is to describe the roles and implementation of confiscation in Jambi court. The sample was taken by purpisive sampling technique and tha date was analysed by qualitative-descriptve technique. From the analysis it is concluded that the roles and the implementation of confiscation in Jambi court depend on the litigants and the accused. It is also found out that the litigants feel assissted during the process of the confiscation. Another finding is that third party frequently take over the ownership of the goods in the dispute. Effor that has been taken to solve this problems is tha the goods are carefully recorded. Besides, there should be collaboration with RT or Kelurahan.